L’intraculturel et la traduction - Potok-Nycz, Magda; Sypnicki, Józef (Studia Romanica Posnaniensia, 2007)
The article takes up the subject of stereotypes within the contractive linguistics and translation area. The authors investigate the presence of cultural and national differences in language systems demonstrating that the fixed set ideas about particular tlings are compactly built in linguistic expressions. The requisites of culture are examined in word components, conceptual models and means of categorization. The selected examples go to prove the individual character of the world representation within different cultures. Other expressions seem to converge or because of language acquisitions (translations) or due to the identical experiences that create the particular forms of understanding the world. In the second part of the article the cultural stereotype is situated in the translation frame. Several translation strategies are proposed. The conclusion, nevertheless, reveals that the stereotypes belong to the linguistic system and, unlike the sense, can be departed from it. Unless the cultural experience of different linguistic communities converges, the stereotypes are untranslatable. The commented patterns of translation procedures demonstrate that the cultural stereotypes do not cross the language barriers in the process of translation.